Evaluation of physical Facilities, Operation and Management Practice in Selective Public Abattoirs in Eastern Oromia, Ethiopia - Birmaduma Gadisa; Yesihak Yusuf; Mohammad Y Kurtu (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
The natures of public abattoirs have a tendency for small market and information on these abattoirs is very limited. This study was conducted with the objectives to assess physical condition, functional infrastructure, daily data record, operational of the abattoirs and analysis the perception of abattoirs works on beef quality determinants at Adama, Dire Dawa and Haramaya University. To know the perception of abattoirs workers on beef quality and operational system survey and discussion was conducted on abattoir works (57) respondents and personal observation. The survey result and personal observation indicated that not all the abattoirs were working to their full potential. Adama, Dire Dawa and Haramaya University abattoirs were established for domestic consumption service. The facilities in abattoir were very few. There were no training for workers related to section hence, operated in traditional ways. No regular health condition check for abattoir workers. In all abattoirs, there were no veterinary laboratory, refrigerator, functional stunning pen, and chilling room, by product collection room, sterilization facilities, hot water service and hazard analytical critical control point (HACCP). Lack of the required instrumentation and facilities in the abattoirs, less attention from the administration and few types of research were carried out on meat quality and abattoir functionality management in all studied abattoirs. There were only limited information was recorded daily. In all abattoirs, there were no carcass classification system on practice, and no breed and age record practices too. Hygiene and sanitation were largerly absent in all abattoirs. Abattoir workers ranked lairage, bleeding methods and carcass handling as important factors to determine meat quality, respectively. Accessing periodically health treatment and train about the section for abattoir worker, updating facilities and peculiarly record all action in abattoir to generate more information for stakeholders.